Determinantes capazes de nortear o voto do povo brasileiro: um estudo histórico sobre o comportamento de políticos e eleitores - Zanoni, Daniela Benato (2006)
The conquering of democracy in Brazil legitimated through the Constitution of 1988, signified the growth of commom autonomy related to political questions and the selection of leaders through election, and was, without a doubt a huge step which effects commom sovereignty and liberty. However, our highly acclaimed democratization was implemented in a country where political culture is deep-rooted in proslavery, patrimonialism, coronelism, that is, we have a framework of a disturbed political history, where to circunvent the law, norms, defraud elections, buy votes, is something which has always occurred with a certain naturalness. The time of election is still seen by some as a time where you have the opportunity to obtain favours or goods in exchange for your vote. Besides, we can still observe that many people vote without even knowing the inherent function of each cargo in office, for example, the function of a Federal Representative or of a Senator. The choice of a voter to vote in a particular candidate or not, can be influenced by the church, school, media, family, though campaign promises, through the candidate s carisma or even the lifestyle in which the voter finds himself in. There are multiples determinants that are capable of guiding a vote, and our study deals exactly with these aspects, which starts recapitulating a little of our political culture and the democratization of the country, that is, the basis where our present day Brazil is resting and ends with a field research, which portraies the behavior of the voters of the city of Ponta Grossa.